The impact of film and film-based activities on the attitudes of English-speaking secondary-school students towards L2 Chinese / Qi Zhang - Zhang, Qi (Universiti Teknologi MARA, Kedah, 2013)
While foreign-language films can provide second language learners with authentic exposure to the target language in a relatively natural context, very few studies have been conducted on the use of film in the teaching of Chinese language and culture. This research project used two film sessions with a group of secondary-school students of Chinese in order to investigate the influence of Chinese film on students’ attitudes towards the study of language from three perspectives: the importance of language study, motivation, and cultural awareness. Comparing pre- with post-event evaluations, the correlation tests show that the integration of film in the classroom can indeed increase motivation to learn Chinese and improve students’ understanding of Chinese culture, but not their perceptions on the importance of language study. Gender was also considered as a factor, and interestingly, compared to their female counterparts, male participants consistently not only report lower motivation, but also demonstrate less cultural awareness after film sessions. The study shows that film may be used effectively in the Chinese language classroom to help learners understand Chinese culture and serve to contextualise the Chinese language, to which British students may have limited real- world access or holiday exposure. The cultural elements conveyed by foreign language films and the audience’s comprehension of these elements could be the starting point for establishing intercultural exchange.